Valuation of metropolitan open space - presenting the research framework - Eric Koomen; Jasper Dekkers; Mark Koetse; Piet Rietveld; Henk Scholten (European Regional Science Association (ERSA), 2005)
The metropolitan landscape consists of green, open areas adjacent to and enclosed by the urban environment. Changes in this landscape are a delicate matter, because they affect sustainability, the environment and the scenic quality, as we see in processes like urban sprawl, intensive outdoor recreation, city expansion and additional investments in infrastructure. More precisely, changes in the supply of open space, both in absolute terms (acreage) and its accessibility are a major concern around metropolitan areas. The lack of a clear monetary value makes green, open areas vulnerable to construction activities and infrastructure. Such use of open space entails the imposition of externalities of certain actors on others, but since the market value of open space does not fully reflect the societal value of open space, these externalities are market failures that call for corrective measures by the public sector in the form of land use interventions or pricing measures. However, as it turns out, failure of the governmental correction impedes effective market co-ordination. Unfortunately, attempts to value open space are virtually non-existent to date. Partly because the valuation of severance and visual intrusion is hampered by many complications, especially difficulties in objective quantification, uncertainties on the impacts on human and ecological communities, and collinearity with other pressures on the metropolitan open space (for example noise disturbance from infrastructure). The development of a research method for the valuation of open space will therefore be an important objective of the project. Incorporation of the public interest in open space in metropolitan planning requires quantitative valuation of this asset. The difficulty with such a valuation is of course that environmental and general societal values are normally not traded on real world markets, and hence no market prices can be observed that would reflect or approximate marginal costs or benefits. An environmental-economic framework will be used to quantify the ecological, economic and societal values of open space in a coherent way. Two complementary methods will be used: revealed preference and stated preference valuation. As it will not be possible to estimate economic values for all different dimensions of open space, the program focuses on those aspects that can be related to the appreciation of individual residents of the metropolitan landscape. These are the so-called 'use values' that humans attach to open space on the basis of their own, direct interest. This focus means that for instance so-called 'intrinsic' environmental values (referring for example to habitat fragmentation and indirectly biodiversity) will be postponed to future research. The program will more specifically concentrate on the added value of the availability of open space on residential property and the valuation of cultural and recreational characteristics of open space by potential visitors.
Keywords: 330